Bone forming capacity of cell‐ and growth factor‐based constructs at different ectopic implantation sites. Issue 2 (22nd April 2014) - Ma, Jinling; Yang, Fang; Both, Sanne K.; Prins, Henk‐Jan; Helder, Marco N.; Pan, Juli; Cui, Fu‐Zhai; Jansen, John A.; van den Beucken, Jeroen J.J.P.
Abstract The aim of this study was to compare the effect of implantation site (i.e., subcutaneous, SQ vs. intramuscular, IM) on bone forming capacity of cell‐based and growth factor‐based scaffolds in athymic nude rats after an implantation period of 8 weeks. Cell‐based scaffolds consisted of porous hydroxyapatite/tricalcium phosphate (HA/TCP) scaffolds seeded with either human adipose tissue‐derived mesenchymal stem cells (AT‐MSCs) only or both AT‐MSCs and human umbilical vein endothelial cells (HUVECs), which were precultured in osteogenic medium for 7 days. Growth factor‐based scaffolds consisted of porous HA/TCP scaffolds with 20 µg preadsorbed bone morphogenetic protein‐2 (BMP‐2). Histological and histomorphometrical analysis were used to assess bone formation. A differentiation experiment was performed in parallel to compare the in vitro osteogenic capacity of cell‐based scaffolds. The results showed that cell‐based scaffolds showed evident osteogenic differentiation in vitro, with only marginal differences between AT‐MSCs only and AT‐MSCs/HUVECs. In vivo, none of the cell‐based scaffolds showed bone formation, irrespective of the site of implantation. In contrast, all growth factor‐based scaffolds showed bone formation at both implantation sites without differences in the amount of formed bone. In conclusion, the results of this study demonstrated that the bone forming capacity of HA/TCP scaffolds with pre‐adsorbed BMP‐2 was equal at different ectopic implantation sites. Further, despite obvious in vitro osteogenic differentiation of AT‐MSCs and AT‐MSCS/HUVECs on HA/TCP scaffolds, no bone formation of these cell‐based scaffolds was observed in vivo. This indicates further investigation on bone formation mechanisms of AT‐MSCs is needed before AT‐MSCs can be used as a cytotherapeutic treatment in clinics. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 439–450, 2015.